Mediating Role of Trust on the Effects of Knowledge Management Capabilities on Organizational Performance - Alaarj, S; Abidin-Mohamed, Z; Ummi Salwa Ahmad Bustamam (Elsevier Science Bv, 2024)
Indexed by WOS